Perspectives of healthcare workers in South Africa on COVID-19 vaccination passports - Claudia J. Jansen van Vuuren; Juan M. Jansen van Vuuren (AOSIS, 2022)
Background: Following the rollout of several effective vaccines against coronavirus disease 2019 (COVID-19), many countries have introduced vaccination passports or certificates as a means of certifying that an individual has been vaccinated against, is immune to, or is presently uninfected with COVID-19. An extensive ethical debate has ensued. Aim: To determine the perspectives of South African healthcare workers (HCWs) on the implementation of COVID-19 vaccination passports (C19VPs) in South Africa (SA). Setting: Healthcare workers working in various fields and practice settings throughout SA were invited to complete an online questionnaire. Methods: An online questionnaire was distributed using convenience sampling via social media platforms to HCWs over a 1-month period, collecting demographic details and responses to 8 Likert-type items regarding agreement with C19VPs, ethical issues and feasibility. Each item was graded from 1 (strongly disagree) to 5 (strongly agree), with grouping of 4 of the 8 items exploring a common theme of C19VPs being a good idea, constituting a score out of 20. Non-parametric tests were performed to determine differences in responses between groups. Results: One thousand HCWs responded to the survey and fulfilled inclusion criteria. The majority (83.2%) of respondents were medical practitioners (MPs). Overall, most (73.5%) respondents agreed that C19VPs are a good idea. Older respondents agreed more strongly than younger respondents (medians 18 and 17, respectively, p = 0.001), and respondents in private practice agreed more strongly than those in state practice (medians 18 and 16, respectively, p = 0.042). The median response was neutral (3) in response to the ethics of C19VPs considering variations in vaccine access and tending towards disagreement (2.5) in disadvantaging poorer people. Most respondents disagreed that vaccine hesitancy would make C19VPs unethical, and responses from provinces with the highest vaccination proportions disagreed more than others with lower vaccination proportion (median 2 compared with 3, p  0.001). There was uncertainty about the feasibility of C19VPs in SA, with older HCWs, non-students, senior MPs and those who thought C19VPs are a good idea being more likely to consider them feasible. Conclusion: The perspectives of HCWs, mainly MPs, about C19VPs in SA were obtained. Further research should focus on vaccine hesitancy and its factors in HCWs and the effect of C19VPs on restrictions, reduction in transmission and benefits on economies and mental health. Contribution: To the authors' knowledge, this is the first survey data published on the perspectives of South African HCWs on C19VPs in the country. Healthcare workers are trusted influencers of vaccination decisions, and their opinion on vaccination certificates may also influence the South African public's perception and acceptance thereof.